Comparison of high flow nasal cannula and non-invasive positive pressure ventilation in children with bronchiolitis: A meta-analysis of randomized controlled trials - Zhong, Zhaoshuang; Zhao, Long; Zhao, Yan; Xia, Shuyue (Frontiers in Pediatrics, 2022)
Background The effects of high‐flow nasal cannula (HFNC) compared to non-invasive positive pressure ventilation (NIPPV) on children with bronchiolitis remain unclear. Methods This meta-analysis was conducted following the preferred reporting items for systematic reviews and meta-analysis (PRISMA) statement. All relevant randomized controlled trials (RCTs) were identified by searching PubMed, EMBASE, Cochrane Library, and Web of Science without time and language limitations. Primary endpoints include the rate of treatment failure, the rate of need for intubation, and the pediatric intensive care unit (PICU) length of stay. Results Five RCTs including 541 cases were enrolled in the meta-analysis. Compared to the NIPPV group, the rate of treatment failure was significant higher in the HFNC treatment group (I2=0.0%, P=0.574; RR 1.523, 95 % CI 1.205 to 1.924, P<0.001). No significant difference was noted in the need for intubation (I2=0.0%, P=0.431; RR 0.874, 95 % CI 0.598 to 1.276, P=0.485) and the PICU length of stay (I2=0.0%, P=0.568; WMD -0.097, 95 % CI -0.480 to 0.285, P=0.618) between the HFNC group and the NIPPV treatment. Conclusions Compared to the NIPPV group, HFNC therapy was associated with a significantly higher treatment failure rate in children suffering from bronchiolitis. The intubation rate and the PICU length of stay were comparable between the two approaches.